Pendampingan Bimbingan Belajar Al Qur’an Dengan Tajwid Untuk Mepersiapkan Ujian Tashih Akhir Santri Di Madrasah Diniyah Al Abror - Ahmad kholilurrohman; Ach. Zayyadi; Moh. Fathorrozi; Fahmi; Hafidzul Ahkam; Muhammad Yunus (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Al-Qur'an learning at Madrasah Diniyah Al Abror faces challenges in the form of a gap between the demands of the final tashih exam and the students' suboptimal level of tajwid mastery. This study aims to analyze the role of guidance and guidance in learning the Qur'an with tajwid in improving the quality of reading and the readiness of students to face the final tashih exam. The study uses a descriptive qualitative method with a participatory approach, where researchers are directly involved in the mentoring process through observation, interviews, and documentation of learning activities based on the Tartila method with a talaqqi and musyafahah approach. The results of the study indicate that structured mentoring through the development of contextual modules, teacher training, and intensive mentoring in small halaqah (Islamic circle) significantly improved students' understanding and pronunciation of tajweed, as demonstrated by improved pre- and post-mentoring evaluation results. The main findings of this study revealed that tajweed learning that emphasizes direct practice, repetition, and habituation is more effective than a purely theoretical approach. The implications of this study indicate that the Tartila-based tajweed mentoring model can be an alternative for applicable, sustainable, and relevant Qur'anic guidance to be integrated into the Madrasah Diniyah curriculum and replicated in other Islamic educational institutions.